Challenges of Integrating an Evidence‐based Intervention in Health Departments to Prevent Excessive Gestational Weight Gain among Low‐income Women. Issue 3 (26th February 2016) - Yeo, SeonAe; Samuel‐Hodge, Carmen D.; Smith, Rachael; Leeman, Jennifer; Ferraro, Amanda M.; Asafu‐Adjei, Josephine K.
Abstract: Objective: To examine health departments' (HD) capacity to adapt and implement an intervention to prevent excessive gestational weight gain. Design and Sample: Seventy‐seven stakeholders (nurses, nutritionists, social workers, health educators, health directors, and multilingual service providers) in nine HDs participated. A descriptive mixed methods approach was used to collect data at workshops held onsite to introduce the evidence‐based intervention (EBI) and discuss its adaptation. Measures: A survey was administered to assess the intervention's fit with the HDs context. Generalized logit mixed models were used to analyze the survey data. The discussions of adaptation were audiotaped and thematically analyzed to identify factors influencing implementation. Results: The majority of stakeholders desired to participate in the training portion of the EBI, but they were reluctant to adopt it, and noted a lack of adequate resources. From the audiotaped narratives, three themes emerged: (1) Patient needs and resources, (2) Perception about adaptability of the EBI, and (3) The complexity of the EBI for pregnant populations. Conclusion: Although the EBI was effective for low‐income nonpregnant populations in southeastern regions, pregnancy and complex antenatal services make this intervention unrealistic to be adapted as a part of prenatal care at HDs.